2013
DOI: 10.1155/2013/375263
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Tacrolimus Toxicity with Phenytoin in Solid Organ Transplant Recipients

Abstract: The pharmacokinetics of tacrolimus are influenced by many factors, including genetic variability, acute infections, liver dysfunction, and interacting medications, which can result in elevated concentrations. The most appropriate management of acute tacrolimus toxicity has not been defined though case reports exist describing the therapeutic use of enzyme inducers to increase tacrolimus metabolism and decrease concentrations. We are reporting on the utilization of phenytoin to assist in decreasing tacrolimus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 18 publications
3
32
0
Order By: Relevance
“…However, tacrolimus concentrations began to decline within 16 hours of initiating phenytoin in this case and were undetectable within 4 days. This rapid reduction in tacrolimus concentration is consistent with other reports of phenytoin induction that have shown tacrolimus concentrations decrease by 6‐fold in 24 hours and greater than 2‐fold in 3 days . It is possible that the tacrolimus concentration was declining prior to initiating phenytoin but we were unable to detect this because the concentration exceeded the upper limit of the assay.…”
Section: What Is New and Conclusionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, tacrolimus concentrations began to decline within 16 hours of initiating phenytoin in this case and were undetectable within 4 days. This rapid reduction in tacrolimus concentration is consistent with other reports of phenytoin induction that have shown tacrolimus concentrations decrease by 6‐fold in 24 hours and greater than 2‐fold in 3 days . It is possible that the tacrolimus concentration was declining prior to initiating phenytoin but we were unable to detect this because the concentration exceeded the upper limit of the assay.…”
Section: What Is New and Conclusionsupporting
confidence: 89%
“…Our patient presented with progressively severe symptoms of tacrolimus neurotoxicity, beginning with calcineurin‐inhibitor pain syndrome characterized by symmetrical pain in the lower extremities, followed by tremors, worsening encephalopathy and psychosis . In the presence of severe symptoms (as reported by others) or persistently elevated tacrolimus concentrations with symptoms (as in this case), use of pharmacologic induction of tacrolimus metabolism is a viable therapeutic option . Phenytoin appears to be the agent of choice for inducing metabolism as it is a strong CYP3A4/5 inducer and has the additional benefit of anti‐seizure activity which is a possible manifestation of tacrolimus neurotoxicity.…”
Section: What Is New and Conclusionmentioning
confidence: 64%
“…In total, 10 publications were identified that utilized pharmacoenhancement with CYP450 enzyme inducing agents for the management of CNI toxicity; 7 reported use of phenytoin and 3 reported use of phenobarbital. No articles using carbamazepine or rifampin were identified (Figure and Table ) …”
Section: Resultsmentioning
confidence: 99%
“…In the current report, we expand on our experience of using phenytoin therapeutically to induce CNI metabolism as a treatment for intoxication (17). Enzyme induction depends on both the half-life of the inducing agent as well as the enzyme being induced (18).…”
Section: Discussionmentioning
confidence: 99%